A mutational analysis of the roles of cytoplasmic domains of the gonadotropin-releasing hormone receptor in coupling and internalization - Pawson, Adam James (Division of Chemical Pathology, 2018)
The G protein-coupled receptor (GPCR) family is the largest group of homologous proteins in the human genome. GPCRs are of prime physiological and medical importance as the actions of a wide range of hormones and drugs are mediated by these receptors. The gonadotropin-releasing hormone (GnRH) receptor is a member of the GPCR family, and plays a central role in the reproductive system. GnRH analogues are used therapeutically in a number of human disorders. All GPCRs contain 7 largely α-helical transmembrane domains. An arginine residue located at the cytosolic boundary of the third transmembrane domain is conserved in all members of the rhodopsin-like subfamily of GPCRs, and is nearly always preceded by an acidic residue (DR motif). This arginine has been proposed to play a critical role in receptor activation. In this thesis, the effects of mutating these residues (Asp¹³⁸ and Arg¹³⁹ respectively, in the mouse GnRH receptor) to neutral amide residues, on coupling of the mouse GnRH receptor, were examined. In addition, the relationship of coupling to internalization in these mutant receptors was explored.